A Survey of the Regulatory Requirements for the Waiver of In Vivo Bioequivalence Studies of Generic Products in Certain Dosage Forms by Participating Regulators and Organisations of the International Pharmaceutical Regulators Programme - Alfredo Garcia Arieta; Craig Simon; Andrew Tam; Gustavo Mendes Lima Santos; Eduardo Agostinho Freitas Fernandes; Zulema Rodríguez Martínez; Clare Rodrigues; Sang Aeh Park; JaYoung Kim; Kwansoo Kim; Ryosuke Kuribayashi; Aya Myoenzono; et al. (Frontiers Media S.A., 2021)
The requirements to waive in vivo bioequivalence studies for immediate release solid oral dosage forms based on the Biopharmaceutics Classifications System (BCS) are well known, and biowaivers[1] for other types of oral dosage forms based on pre-defined criteria may also be acceptable. Similarly, biowaivers for dosage forms such as injectable products may also be allowed if certain criteria are met. The current paper summarises the biowaiver requirements for oral solutions and suspensions, soft gelatin capsules and injectable products (intravenous injections, subcutaneous and intramuscular injections, emulsions for injection and micellar solutions for injection) among the participants of the Bioequivalence Working Group for Generics (BEWGG) of the International Pharmaceutical Regulators Programme (IPRP). A review of the requirements indicated that there was a trend towards convergence when the dosage form became less complex; however, the most common approach used by each of the jurisdictions was a case-by-case approach given that most jurisdictions do not have well defined guidelines to support all possible scenarios. Even in the simplest case of intravenous solutions, the acceptability of qualitative changes in excipients differ between the IPRP members.  Notwithstanding the differences, the dissemination of the information is a first step towards regulatory convergence regarding biowaivers for certain dosage forms and should be useful for pharmaceutical companies currently developing generic medicinal products for IPRP jurisdictions.